2013
DOI: 10.1093/nar/gkt726
|View full text |Cite
|
Sign up to set email alerts
|

Yeast ribosomal protein L7 and its homologue Rlp7 are simultaneously present at distinct sites on pre-60S ribosomal particles

Abstract: Ribosome biogenesis requires >300 assembly factors in Saccharomyces cerevisiae. Ribosome assembly factors Imp3, Mrt4, Rlp7 and Rlp24 have sequence similarity to ribosomal proteins S9, P0, L7 and L24, suggesting that these pre-ribosomal factors could be placeholders that prevent premature assembly of the corresponding ribosomal proteins to nascent ribosomes. However, we found L7 to be a highly specific component of Rlp7-associated complexes, revealing that the two proteins can bind simultaneously to pre-ribosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 56 publications
4
17
0
Order By: Relevance
“…Interestingly, we observe increased modification of 2 nt in the Cic1 interaction site, which may indicate a change in the binding of Cic1. Moreover, we observe changes in reactivity at a common subset of nucleotides that would be consistent with a shift from ring structure to hairpin structure of ITS2 (Granneman et al 2011;Babiano et al 2013;Dembowski et al 2013). Thus, in the absence of the N-terminal extension of L8, the binding of some assembly factors that interact with ITS2 are distorted, which may cause ITS2 to form a structure that inhibits its processing after C 2 cleavage.…”
Section: Resultssupporting
confidence: 58%
“…Interestingly, we observe increased modification of 2 nt in the Cic1 interaction site, which may indicate a change in the binding of Cic1. Moreover, we observe changes in reactivity at a common subset of nucleotides that would be consistent with a shift from ring structure to hairpin structure of ITS2 (Granneman et al 2011;Babiano et al 2013;Dembowski et al 2013). Thus, in the absence of the N-terminal extension of L8, the binding of some assembly factors that interact with ITS2 are distorted, which may cause ITS2 to form a structure that inhibits its processing after C 2 cleavage.…”
Section: Resultssupporting
confidence: 58%
“…CRAC analysis revealed that Erb1 and Nop7 cross-link to sequences in domain I and domain III of 25S rRNA, respectively (26). Last, Cic1, Nop15, and Rlp7 cross-link to sequences in ITS2 and the ITS2-proximal stem (26,30,69).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been previously pointed out that eukaryotic RNA elements and eukaryotic r-proteins and their extensions localize together on the solvent-exposed side of the ribosome and make numerous contacts with each other (Ben-Shem et al 2011). Several eukaryote-specific assembly factors such as Rlp7, Arx1, Rrp5, and Nop7 bind to ES (Granneman et al 2011;Bradatsch et al 2012;Babiano et al 2013;Dembowski et al 2013;Lebaron et al 2013). Combined with our observation about similar functions in ribosome assembly for eukaryote-specific ES31Δ L and the eukaryote-specific extension of L8, these lines of evidence raise the possibility that eukaryote-specific protein-RNA elements may have coevolved, and perform similar functions in the cell.…”
Section: Viable Es Mutants Can Synthesize Mature 25s Rrnamentioning
confidence: 99%